Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Pelanggan di Toko Outdoormu Kota Bima - Nurul Inayah; Umar Sagaf; Dinah Husniah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of product quality and price on consumer purchase intention at outdoorMU Store in Bima City. The background of this research is based on the growing trend of outdoor activities, which drives the expansion of the outdoor gear industry, particularly in Bima, an area with great natural tourism potential. The research employed an associative quantitative approach with purposive sampling involving 68 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25. The results show that both product quality and price have a positive and significant effect on consumers’ purchase intention, both partially and simultaneously. These findings offer strategic implications for store management to continuously improve product quality and set competitive prices to maintain customer loyalty in an increasingly competitive market.